(untitled) (Journal of Business Management and Accounting, 2015)
The Government Transformation Programme has become the central issue among the public. For any government to retain its popularity, changes are needed to provide more vibrant, dynamic, and progressive services to its client, customer, and stakeholders. Therefore, implementing McKinsey approach is one mechanism to realise the transformation programme. Implementing McKinsey approach has long been practised by various organisations in adding value to delivery and improving performance. This article demonstrates findings of the four out of seven McKinsey approach elements implemented in two government departments in Malaysia. The survey method was conducted in this study on respondents comprising all the stakeholders dealing in the everyday transactions with the government departments, including suppliers, vendors, and many more. All the questionnaires were analysed and findings explained in greater detail. The four McKinsey elements included strategy, structure, system, and shared values (4S).A comparison was made between the results of the 4S from both agencies. Interestingly, the results illustrated how the government departments transformed their operational services by getting the whole organisation to put great efforts to undergo the overall process. The results also indicated that for a government department to undergo transformation, staff’s attitude toward changes, behaviour, and knowledge are crucial in making the process a successful one. Further elaboration on outcomes of each McKinsey elements is discussed in detail. The findings would become a guideline for future research dealing with elements of McKinsey approach, as well as serve as a reference for the betterment of any organisation that wants to apply the transformation agenda.